The Relationship between Maternal Knowledge and Attitude with Children's Readiness for Toilet Training in Children of PAUD Alumna Islamic School Sukajadi - Ani Triana; Wahyuni, Sri; Damayanti, Ika Putri (Fakultas Kedokteran, Universitas Papua, 2025)
Toilet training is an effort to educate children to manage urination and defecation independently. Toilet training can be initiated at various developmental stages, typically between the ages of 18 months and 4 years. The process of training for urination and defecation requires physical, mental, and intellectual readiness, with the goal that the child will eventually be able to control these functions independently. The purpose of the study was to determine the relationship between maternal knowledge and attitudes with children's readiness for toilet training in Alumna Islamic School Sukajadi PAUD children. This research employed a quantitative analytic approach with a cross-sectional design. The sample consisted of 50 mothers with children enrolled in the playgroup class, selected using a total sampling technique. The data were analyzed using univariate analysis with frequency distribution and bivariate analysis with the Chi-square statistical test. The results showed a significant relationship between maternal knowledge and the child's readiness for toilet training (p-value = 0.001 < α = 0.05), as well as a significant relationship between maternal attitude and toilet training readiness (p-value = 0.021 < α = 0.05). It is expected that schools can conduct socialisation and education to parents about toilet training preparation and improve facilities for child-friendly toilet training for students at PAUD Alumna Islamic School.